PENALARAN MORAL HUBUNGANNYA DENGAN FAKTOR-FAKTOR BUDAYA SISWA - Budiningsih, C. Asri (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract This study aims to describe the students' characteristics including the stages and/or degrees of their moral reasoning, existential belief, empathy, and social role taking. This study was categorized as descriptive-correlational research. SLTP and SMU students in Yogyakarta constitute the subject population. Samples were drawn using a stratified random sampling technique. Data gathered using the test technique: (1) Moral Reasoning Test; (2) Existential Belief Test: (3) Empathy Test (4) Social Role Test. The data were collected from 480 students. Data were analyzed using averages and percentages to uncover the students' characteristics, pearson-correlation technique to examine the relationship among variables, and anova technique to examine differences of variables. Results of the study leads to the following conclusion: (1) moral reasoning tends to operate on stage III, namely harmony oriented or good boy-nice gorl oriented; (2) existential belief tends to operate on stage III, namely synthetic-conventional faith; (3) empathy tends to operate on degree III which means that in responding others they tend only to reflect the others' surface feelings;(4) social role taking tends to operate on degree III, which is moderate; (5) the relationship between existential belief and moral reasoning is negative (6) the relationship between empathy is negative and insignificant (7) the relationship between social role taking and moral reasoning is negative and insignificant (8) there was no difference tends of moral reasoning between SLTP and SMU students (9) there was no difference tends of moral reasoning between the students whose parents have same religion and some students whose parents of different religion (10) there was no different tends of moral reasoning between the students whose parents have same races and the students whose parents are of different races. Keywords: students' characteristics, culture, moral reasoning, extential belief, empathy, social role taking